Analisis Sikap Perilaku Disiplin Siswa Kelas IV dan Faktor yang Mempengaruhinya di SDN Gili Anyar - Kurniawati, Lailatul Ayu (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
Student discipline is an important aspect of character development in elementary education because it is related to students’ ability to obey rules, manage time, take responsibility, and maintain order during learning activities. This study aims to analyze the disciplinary behavior of fourth-grade students and identify the factors influencing such behavior at SDN Gili Anyar. This study employed a descriptive qualitative approach. The research subjects consisted of the fourth-grade teacher and five fourth-grade students selected through purposive sampling from a total of 28 students. Data were collected through observation, interviews, and documentation. Data analysis employed the interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was examined through source and technique triangulation. The findings indicate that the disciplinary behavior of fourth-grade students was generally good. Most students arrived at school on time, complied with school rules, returned to class after breaks according to schedule, and participated in learning activities in an orderly manner. However, several students were still occasionally late and showed minor violations, particularly related to incomplete school attributes. The main internal factor influencing student discipline was self-awareness, while external factors included teacher modeling, classroom agreements, family environment, school rules, and peer influence. These findings indicate that student discipline is formed through the interaction between internal awareness and consistent environmental support.
Keywords: student discipline; character education; elementary school; internal factors; external factors